Peningkatan Program Studi Melalui Perencanaan Strategis dalam Pemenuhan Kebutuhan Sumber Informasi Kajian Keilmuan Sivitas Akademika (Analisis Pelaksanaan di Perpustakaan Sekolah Tinggi Agama Islam Negeri Curup) - Iswanto, Rahmat (Perpustakaan STAIN Curup, 2017)
The successful implementation of education in the Study Program is something that continues to be realized and improved in order to prepare the quality of graduates the better. Success in this case is also supported by many important factors and elements. Important factors consist of internal and external factors of Study Program. Internal factors include the quality of inputs or students of the Study Program, the quality of the teaching staff, the established and tested curriculum, adequate laboratory and classroom space, and evaluation of the availability of information resources for the study study. External factors of the Study Program include the carrying capacity of the parent institution, cooperative activities, information provider institutions such as library resources, and others. The library is quite rightly referred to as the heart of the college by looking at its function as a provider of information resources that support the provision of basic literature and supporting the implementation of lectures. The more complete and good the information resources provided by the library the better the fulfillment of literature needs for the Study Program. The better the study program literature available in the library the better the progress of the Study Program. This study examines the problem of how strategic planning relates to the needs of users (academicians) in STAIN Curup. Scientific examination of the above problems through the process of descriptive qualitative research using related theories and provide additional data description in the form of information on the implementation of the process of collecting libraries and librarian tasks that have been implemented in the Library STAIN Curup last two years. The analysis is obtained with information from the actors by looking at the constraints and collisions of the ideal theory. Strength of STAIN Curup Library owned in the implementation of strategic plan of routine budget, adequate human resources, supporting applications, and internet network. While other things are very potential to be manifested. Obstacles encountered can be overcome by regular evaluation process, good communication, support of the management and the provision of facilities and special human resources